Decision-making in acute viral bronchiolitis: a universal guideline and a publication gap - Meyburg, Jochen; Ries, Markus (PLOS ONE, 2020)
BACKGROUND: Acute viral bronchiolitis is very common in infants and children up to 2 years. Some patients develop serious respiratory symptoms and need to be hospitalized. In 2014, the American Academy of Pediatrics (AAP) published a guideline on acute bronchiolitis which has gained global acceptance. We hypothesized that a publication gap, which is increasingly perceived in clinical medicine, might have also affected these universal recommendations. - METHODS: We determined the proportion of published and unpublished studies registered at ClinicalTrials.gov that were marked as completed by October 1st 2018. The major trial and literature databases were used to search for publications. In addition, the study investigators were contacted directly. - RESULTS: Of the 69 registered studies on the treatment of acute viral bronchiolitis, only 50 (72%) have been published by November 2019. Published trials contained data from n = 9403 patients, whereas n = 4687 patients were enrolled in unpublished trials. Median time to publication was 20 months, and only 8 of 50 trials were published within 12 months after completion. Only 40% of the clinical trials that were completed after the release of the AAP guideline were subsequently published as compared to 80% before 2014. - CONCLUSION: There is a significant publication gap regarding therapy of acute viral bronchiolitis that may have influenced certain recommendations of the AAP guideline. In turn, recommendations of the guideline might have discouraged investigators to publish their results after its release.
Gesehen am 21.08.2020